Development and PLS-SEM Validation of a Multidimensional Instrument for Medication Adherence in Indonesian T2DM Patients - Ivans Panduwiguna; Rani Sauriasari; Ratu Ayu Dewi Sartika; Woro Riyadina (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2026)
There are several instruments available to assess adherence levels, most have not comprehensively measured the determinants that influence patient behavior, especially in the context of the Indonesian culture. This study aims to develop and test the psychometric validity of a new instrument that can measure the determinants of medication adherence in T2DM patients in Central Bogor, Indonesia. This Study using the development method borg and gall method and expert panel, the instrument was tested for content validity using the content validity ratio (CVR) and content validity index (CVI). The population consisted of patients enrolled in the Noncommunicable Disease Risk Factors Study in Bogor City, based on data from the Health Development Policy Agency. Using purposive sampling of 170 patients with type 2 diabetes (T2DM) in Central Bogor. Structural model evaluation was performed using the partial least squares structural equation modeling (PLS-SEM) approach. The final instrument consisted of 7 constructs and 40 items. All items had adequate factor loading values (≥0.678), and all constructs showed good reliability (α = 0.678−0.975; CR > 0.8; AVE > 0.5). The results of the structural analysis showed significant relationships between the constructs and compliance. For example, perceived barriers played a negative role in compliance (β = −0.573; p < 0.001). The model fit index also showed adequate results (SRMR = 0.061; RMSEA = 0.047; NFI = 0.914). The developed instrument has strong psychometric characteristics and its use is feasible for the identification of factors that influence medication adherence in T2DM patients in Indonesia.